Nurses’ Satisfaction with a Web-Based Application for Calculating Nursing Staff Based on Patient Dependency Levels and Unit Workload in Hospitals - Afriani, Tuti; Rr. Tutik Sri Hariyati; Hanny Handiyani; Dyah Fitri Wulandari (Caring: Indonesian Journal of Nursing Science, 2025)
Complaints from nurses are often received by nursing managers regarding staff shortages, which leads to increased workload. Determining the unquantifiable level of workload poses a challenge, as the head nurse cannot accurately assess the number of staff shortages in the hospital room. Therefore, this study aims to develop a web-based application for the calculation of nursing staff needs based on patient dependency levels and unit workload. The application is accessible through both mobile and web platforms. A pre-experimental one-shot case study design, including 25 nurses, was used at a hospital in West Java. Measurements were conducted only during the post-test phase. The results showed that the majority of respondents were female (80%), who held a Diploma degree (76%), and worked as managers (48%). The average age of respondents was 34.3 ± 7.27 years, with a median experience of 5.0 ± 728 years. Generally, nurses' satisfaction with the application was at a moderate satisfaction, with an average satisfaction rate of 72.4%. A more detailed breakdown showed satisfaction scores of 74%, 71.4%, 75%, 70%, and 70.8% for content, format, accuracy, timeliness, and ease of use, respectively. Satisfaction with the application needs to be improved, specifically for timeliness and ease of use. This application was developed as a potential method for efficiently assessing staffing needs. Providing adequate training for nurses is essential to enhance the effectiveness and usability of the application in hospital settings.